Projectile penetration of thin aluminium plate - Pearson, Giles Christopher (Department of Mechanical Engineering, 2023)
The study of thin plate penetration has long been hampered by the lack of experimental data and that which has been reported is concerned mainly with displacement time records of the projectile and target responses to impact. In the present study two new techniques have been developed to monitor: the penetration process. The first records a specific particle deceleration in the projectile during penetration from which the forces of impact can be derived and the second records the growth of the projectile target contact area. Whereas data obtained from the first method can only describe the projectile's response to impact, it is possible by means of the second method to interrelate the projectile and target responses. The combination of these two techniques therefore provides a powerful tool by which thin plate impacts can be studied. To understand the nature of the experimental results which have been obtained, an empirical model of thin plate penetration has been developed. This analysis is based on the assumption that on impact, the target responds as a thin rigid plastic membrane and has been found to model the penetration process reasonably well for D/H ratios greater than 10.